PENGARUH METODE EKSTRAKSI MASERASI DAN SOKLETASI TERHADAP STANDARDISASI PARAMETER SPESIFIK DAN NON SPESIFIK EKSTRAK ETANOL BIJI PEPAYA (Carica papaya L.) - Alda Safitri Maria Ulfa; Emelda Emelda; Muhammad Abdurrahman Munir; Nanik Sulistyani (Jurnal Insan Farmasi Indonesia, 2023)
Papaya plant (Carica papaya L.) is a plant of Caricaceae family. Papaya has many health benefits, such as papaya seeds (Carica papaya L.) which can be used as medicine. This research is purely experimental with a research design to determine effect of maceration and soxhletation extraction methods on the standardization of specific and non-specific parameters of papaya seeds (Carica papaya L.). The result show  extraction method did not affect the standardization of specific parameters (total phenolic content) which showed no significant difference to the total phenolic content (standard gallic acid) as seen from the results of the analysis p sig 0.184 (p>0.05). The extraction method showed that there was a significant difference to the water content with a p sig of 0.046 (p <0.05). The total ash content and specific gravity showed a significant difference to the extraction method with a p sig 0.000 (p <0.05). The conclusion of this study is that there is an influence of maceration and soxhletation extraction methods on non-specific parameters, moisture content, total ash content and specific gravity. Meanwhile, there was no effect of soxhletation and maceration extraction methods on specific parameters total phenolic content.